1973
DOI: 10.1161/01.res.33.5.573
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Diffusible Tracers and Carbonized Microspheres in the Left Ventricle of Isolated Dog Hearts

Abstract: Microspheres of different sizes, '-"'I-labeled antipyrine (I-Ap), and 4 -KCl or 86 RbCl were injected into the aortic inflow of isolated, Langendorff, perfused, nonworking dogs hearts at blood flows of 1.3-4.8 ml/min g~'. After 15 seconds to 5 minutes, the left ventricle was sectioned into about 300 ordered pieces, and the amount of each tracer was determined. For all tracers, the relative density of deposition was generally higher in the endocardial region, except in one heart in which the aortic pressure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
98
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(109 citation statements)
references
References 34 publications
9
98
0
Order By: Relevance
“…The technique developed by Yipintsoi et al merits special consideration for use as a standard for estimating heterogeneity. 40 They cut the hearts into four or five slices from apex to base. Each slice of left ventricle was cut into 8 wedges at 45° angles, and each wedge cut into 10-12 sections from endocardium to epicardium, as shown in Fig.…”
Section: Effects Of Heterogeneity Of Flow On Washoutmentioning
confidence: 99%
“…The technique developed by Yipintsoi et al merits special consideration for use as a standard for estimating heterogeneity. 40 They cut the hearts into four or five slices from apex to base. Each slice of left ventricle was cut into 8 wedges at 45° angles, and each wedge cut into 10-12 sections from endocardium to epicardium, as shown in Fig.…”
Section: Effects Of Heterogeneity Of Flow On Washoutmentioning
confidence: 99%
“…However, when analysis of the local deposition density of microspheres [2][3][4][5] and diffusible plasma flow markers [6][7][8] in volume elements of a few millimeters diameter showed that the local flow distribution within individual hearts is markedly heterogeneous, covering a range from 20% to 200% of the mean value. This flow heterogeneity is remarkably stable over periods of several hours, 4 even if the heart is intermittently stimulated.…”
mentioning
confidence: 99%
“…Over the size range of 10-15 m the bias in size of microspheres compared to erythrocytes appears unimportant for most organs (12,13). To avoid the risk of arteriovenous shunting 15 m microspheres have become the standard choice.…”
Section: Resultsmentioning
confidence: 99%